Application of Logistic Function for Analysis of Marginal Value Diminishing Laws - Girdzijauskas, Stasys; Štreimikienė, Dalia (Ekonomika, 2007)
There are several very important economic theories related to the analysis of consumers’ and producers’ behavior under the same laws of diminishing marginal values. The laws of diminishing marginal values associated with limited resources can be mathematically formalized by applying the logistic functions which have been primarily developed for the description of population growth under conditions of limited resources and clearly indicate the limits of this growth. When the use of resources reaches the limit of saturation, the exponential law which is usually applied in economic theory to describe economic growth cannot be applied. The law of diminishing returns, the law of diminishing utility, etc. indicate that under conditions of saturation when we have so many units of some product that an additional unit of that product does not provide for any satisfaction or investments are so huge that additional investment would not provide any increase in output when all other factors are constant, i. e. limited, for the development and forecast of economic systems. the logistic model can be successfully applied. If there are no limits in consumption structure or in the structure of production factors, the law of diminishing marginal values is not valid. In this case, the logistic function can be applied for the description of economic laws, rather than certain restrictions being imposed on the system.